Analysis of the Use of Android in Human-Computer Interaction Learning on the Learning Outcomes of Informatics Engineering Education Students - Teguh Ikhsani Putra (Universitas Negeri Padang, 2025)
This study investigates the influence of Android device utilization in Human–Computer Interaction (HCI) learning on student learning outcomes in the Informatics Engineering Education program at STKIP Al-Maksum. A quasi-experimental design was employed to compare an experimental group, which used Android-based activities such as interface prototyping with Android Studio and Figma, with a control group that relied on traditional lecture-based methods. Data were collected through pre-test and post-test assessments, questionnaires, observations, and interviews, and analyzed using descriptive statistics, independent t-test, linear regression, and thematic analysis. The findings indicate that the experimental group achieved an average improvement of 20.5 points (from 65.2 to 85.7), which was significantly higher than the 10.5-point increase observed in the control group (from 64.8 to 75.3). Independent t-test analysis confirmed a significant difference between groups (p < 0.001), while linear regression revealed that Android usage intensity predicted 45% of the variance in learning outcomes. Qualitative results further highlighted two key themes: interactive benefits (reported by 70% of participants) and technical challenges (30%). This study concludes that Android-based learning can significantly enhance HCI learning outcomes through interactive approaches, with technology training serving as an important supporting factor. However, technical challenges remain and should be addressed to ensure optimal implementation.